RETRACTED: Safety Evaluation of Antituberculosis Drugs During Pregnancy: A Systematic Review and Meta-Analysis - Zhou, Xiaomei; Fang, Guoying; Xie, Yaqing; Wei, Anqi; Huang, Feixiang (Frontiers in Surgery, 2022)
BACKGROUND Endocrine and metabolic dysfunction and decreased immunity in pregnant women are the population of tuberculosis, especially in patients infected with HIV at the same time. Anti-tuberculosis drug prophylaxis is effective in reducing tuberculosis infection in pregnant women and fetuses after pregnancy, but its safety is still worthy of in-depth discussion. In this study, we conducted a systematic review and meta-analysis of reports on the use of anti-TB drugs during pregnancy in recent years to provide evidence for clinical diagnosis and treatment.Methods Pubmed, Embase, WEB OF SCIENCE database, Ovid and clinicaltrials.gov were searched. The clinical randomized controlled studies and cohort studies on the use of anti-tuberculosis drugs during pregnancy published in the database from January 2000 to September 2021 were performed using STATA16.0 software after screening the qualified literatures.Results On the basis of the initial search of 408 articles, this study included a total of 8 articles and 2563 patients after screening; meta-analysis results showed that the preventive treatment with anti-tuberculosis drugs did not increase the incidence of serious maternal adverse events [RR=0.99, 95%CI(0.88,1.12), Z=-0.108, P=0.914], did not increase drug hepatotoxicity [RR=1.13, 95%CI(0.90,1.43), Z=1.071, P=0.284], did not increase the incidence of peripheral nerve disease [RR=1.52, 95%CI(0.85,2.71), Z=1.412, P=0.158], did not increased maternal mortality [RR=0.67, 95%CI(0.27,1.70), Z=-0.840, P=0.401], and could significantly reduce adverse pregnancy outcomes [RR=0.78, 95%CI(0.68,0.89), Z=-3.581, P<0.0001].Discussion The use of anti-tuberculosis drugs for preventive treatment during pregnancy is safe and can obtain better pregnancy outcomes.